Study on Mechanical Properties of LM 6 Aluminium Alloy Reinforced With Ground Granulated Blast Slag (GGBS) Particles. (2020) - Kumar Ch, Manoj; Rajendra Kumar, N.; Thenarasu, M.
Abstract: Ground Granulated Blast Furnace Slag particles of size 20-50μm were incorporated in LM 6 aluminium alloy by using stir casting method. The weight percentage of GGBS particles is varied by 1.5%, 2.5%, and 3.5 %. Presence of GGBS particles can be observed in matrix material by SEM and EDX analysis. The hardness of the composites increased by 35.8 % for 3.5 wt.% GGBS particles when compared with base LM 6 alloy. The tensile strength of the composites increased by 63.6 % for 3.5 wt.% composite when equated to the unreinforced alloy. Impact energy is and Percentage of elongation decreased as increasing in wt. % of GGBS